2021
DOI: 10.1016/j.cell.2021.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Cohesin mediates DNA loop extrusion by a “swing and clamp” mechanism

Abstract: Structural maintenance of chromosomes (SMC) complexes organize genome topology in all kingdoms of life and have been proposed to perform this function by DNA loop extrusion. How this process works is unknown. Here, we have analyzed how loop extrusion is mediated by human cohesin-NIPBL complexes, which enable chromatin folding in interphase cells. We have identified DNA binding sites and large-scale conformational changes that are required for loop extrusion and have determined how these are coordinated. Our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
144
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(168 citation statements)
references
References 45 publications
24
144
0
Order By: Relevance
“…By contrast, our result that ATP binding is the step-generating process is in good agreement with cryo-EM results on cohesin ( 20 , 21 , 55 , 56 ) and with AFM data on condensin that showed a transition from an extended state to a hinge-engaged state upon ATP binding ( 18 ). In addition, our results are also consistent with recent AFM and single-molecule FRET study on human cohesin that showed that ATP-binding promotes head domain engagement that provides DNA binding sites via hinge-head interaction ( 57 ). Importantly, our finding further agrees with results found in vivo , which reported that the hinge domain of cohesin engages with the globular domain to form a B shape ( 58 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…By contrast, our result that ATP binding is the step-generating process is in good agreement with cryo-EM results on cohesin ( 20 , 21 , 55 , 56 ) and with AFM data on condensin that showed a transition from an extended state to a hinge-engaged state upon ATP binding ( 18 ). In addition, our results are also consistent with recent AFM and single-molecule FRET study on human cohesin that showed that ATP-binding promotes head domain engagement that provides DNA binding sites via hinge-head interaction ( 57 ). Importantly, our finding further agrees with results found in vivo , which reported that the hinge domain of cohesin engages with the globular domain to form a B shape ( 58 ).…”
Section: Discussionsupporting
confidence: 91%
“…Our data are also in good agreement with a DNA scrunching model that we recently hypothesized based on these AFM data ( 18 ), where condensin anchors itself to DNA using the safety belt of the Ycg1-Brn1 domains (Figure 4I , i ) ( 11 , 59 ), whereupon the hinge domain binds to a proximate region of the DNA, and ATP binding induces a transition from an extended O shape to a collapsed hinge-engaged B shape, thereby pulling the hinge-bound DNA to the globular domain (Figure 4I , ii), which establishes a step in the loop extrusion process. In support of this concept, previous studies showed that ATP binding induces the dimerization of the head domains, forming a positively charged cavity that is able to bind DNA ( 21 , 24 , 57 , 60 , 61 ). The low stalling force that we observed is consistent with a type of a motor mechanism that involves a Brownian ratchet motion of the flexible SMC arms that underlies the hinge to globular domain step ( 62 ).…”
Section: Discussionmentioning
confidence: 75%
“…By contrast, our result that ATP binding is the step-generating process is in good agreement with cryo-EM results on cohesin (20,21,55,56) and with AFM data on condensin that showed a transition from an extended state to a hinge-engaged state upon ATP binding (18). In addition, our results are also consistent with recent AFM and single-molecule FRET study on human cohesin that showed that ATP-binding promotes head domain engagement that provides DNA binding sites via hingehead interaction (57). Importantly, our finding further agrees with results found in vivo, which reported that the hinge domain of cohesin engages with the globular domain to form a B shape (58).…”
Section: Atp Binding and Hydrolysis Relate To Two Distinct Mechanistic Processessupporting
confidence: 92%
“…WPL1 deletion increased Smc3 levels in smc3-K112,113R cells ( Figure 9C and D ), but to a lesser extent than in the eco1-aa background ( Figure 3A ). Although the reasons for this are unclear, the finding that these residues are involved in binding DNA ( Shi et al, 2020 ; Bauer et al, 2021 ) suggests that the amino acid substitutions may themselves perturb cohesin loading or translocation, in addition to preventing acetylation by Eco1. Nevertheless, although introduction of the smc3-K112,113R mutation into wpl1Δ cells only slightly reduced Smc3 levels at centromeres, it greatly reduced Smc3 levels at pericentromeric borders and arm sites ( Figure 9C and D , compare wpl1Δ and smc3-K112,113R wpl1Δ ).…”
Section: Resultsmentioning
confidence: 99%